Simple and rapid detection of Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans by loop-mediated isothermal amplification assay (Bangladesh Journal of Medical Science, 2018)
Background: Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans are two main causative agents associated with periodontitis, an inflammatory reaction of tissues around the teeth. The aim of this study was to develop and evaluate the loop-mediated isothermal amplification (LAMP) assay for simple and rapid detection of P. gingivalis and A. actinomycetemcomitans.Methods: A total of ten subgingival plaque and saliva samples were evaluated to detect the presence of both bacteria by LAMP and PCR assays. Two sets of six primers each were designed to amplify pepO and dam gene. The LAMP assay was carried out using a Loopamp DNA amplification kit in 25 μl volumes. The reaction mixture was incubated at 65oC for 60 minutes and terminated at 80oC for 5 minutes in heating block. The amplification reactions were visualized using naked eye detection and by agarose gel electrophoresis. The sensitivity of the LAMP assay was investigated ranging from 10 μg to 100fg of P. gingivalis(ATCC 33327) and A. actinomycetemcomitans (ATCC 33384).Results: The lowest detection limit of both LAMP and PCR methods were 1 ng and 10 ng of DNA, respectively. When crude template of subgingival plaques were used, P. gingivalisand A. actinomycetemcomitans were tested80% (8/10) and 60% (6/10) positive respectively through LAMP detection. Whereas by PCR, P. gingivaliswas tested 40% (4/10) positive and no significant detection rate for A. actinomycetemcomitans. When a crude template of saliva was used, P. gingivalisand A. actinomycetemcomitans were tested 70% (7/10) and 30% (3/10) positive respectively through LAMP detection. Whereas, when using PCR, there was no significant detection rate for P. gingivalisand A. actinomycetemcomitans.Conclusion: The LAMP assay using a crude template offers greater advantage as it is simple, rapid and cost-effective to detect periodontal pathogens.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.402-410